Audio Reviews. (Popular Music & Society, 2007)
The article reviews several music releases including "Live From Austin TX," by Delbert McClinton, "Reinvention Highway," by Johnny Rivers and "Songs for Parents Who Enjoy Drugs," by Hamell on Trial.